Netupitant-palonosetron (NEPA) for preventing chemotherapy-induced nausea and vomiting: from clinical trials to daily practice - Aapro, Matti S.; Jordan, Karin; Scotté, Florian; Celio, Luigi; Karthaus, Meinolf; Roeland, Eric (Current cancer drug targets, 2022)
Chemotherapy-induced nausea and vomiting (CINV) is a common adverse event associated - with many anticancer therapies and can negatively impact patients' quality of life and potentially - limit the effectiveness of chemotherapy. Currently, CINV can be prevented in most patients with - guideline-recommended antiemetic regimens. However, clinicians do not always follow guidelines, - and patients often face difficulties adhering to their prescribed treatments. Therefore, approaches to - increase guideline adherence need to be implemented.
Gesehen am 10.01.2023